Two-dimensional modeling of plasma confinement in a toroidal electromagnetic trap - Lavrent’ev, O.A.; Maslov, V.A.; Germanova, S.V.; Shevchuk, B.A.; Krutko, N.A. (Вопросы атомной науки и техники, 2007)
Two-dimensional modeling of plasma confinement in a toroidal electromagnetic trap with transverse magnetic slits is carried out. The spatial distributions of electrons and ions density, magnetic and electrostatic potentials are obtained. Diamagnetic currents of electrons and ions, responsible for shielding of a vacuum magnetic field in plasma, and borders of the superseded vacuum magnetic field are determined. Проведено двомірне моделювання утримання плазми в тороідальній електромагнітній пастці з поперечними магнітними щілинами. Отримані просторові розподіли густини електронів і іонів, магнітного та електростатичного потенціалів. Визначені діамагнітні токи електронів та іонів, відповідальні за екранування вакуумного магнітного поля в плазмі, і межі витиснутого магнітного поля. Проведено двумерное моделирование удержания плазмы в тороидальной электромагнитной ловушке с поперечными магнитными щелями. Получены пространственные распределения плотности электронов и ионов, магнитного и электростатического потенциалов. Определены диамагнитные токи электронов и ионов, ответственные за экранирование вакуумного магнитного поля в плазме, и границы вытесненного магнитного поля.